Integrating life cycle assessment and electrochemical modeling to study the effects of cell design and operating conditions on the environmental impacts of lithium-ion batteries. (July 2021) - Lybbert, M.; Ghaemi, Z.; Balaji, A.K.; Warren, R.
Abstract: Lithium-ion batteries have been the focus of many life cycle assessment studies in recent years due to the rapid growth in demand for lithium-ion batteries raising concern over their environmental impacts. This work demonstrates a new approach for reverse life cycle assessment of lithium-ion batteries that couples first-principles and semi-empirical electrochemical modeling with traditional battery life cycle assessment methodology. The approach enables systematic evaluation of battery design parameters as well as operating conditions on the environmental impacts of lithium-ion batteries. Results are presented for the effects of electrode thickness, porosity, discharge rate, and ambient temperature on the global warming potential and mineral depletion potential of lithium iron phosphate-graphite batteries. The effect of these design parameters and operating conditions on battery energy density and cycle life are considered for the first time as part of a battery life cycle assessment. The results identify specific values of electrode thickness and porosity that minimize the environmental impacts of lithium iron phosphate batteries, and the dependence of these values on battery discharge rate. Ultimately, it is envisioned that the electrochemical life cycle assessment approach presented in this work will provide a foundation for future studies exploring the effects of battery design and operation on life cycle environmental impacts of a variety of lithium-ion and beyond lithium-ion cell chemistries, such that the environmental impacts of batteries in specific applications can be minimized. Highlights: First-principles electrochemical modeling is integrated with battery life cycle assessment for the first time. Specific values of electrode thickness and porosity that minimize lithium-ion battery environmental impacts are presented. Optimum cell designs for minimizing life cycle environmental impacts are presented for various C-rates and temperatures.